Nieprzyjaciele w Psalmach - Łach, Stanisław (The Biblical Annals, 2017)
There often arises the problem of „enemies” in the Psalms persecuting the psalmists. Since in the studies the Psalmists are no longer identified with David there exists an unceasing discussion among scholars not only about the identification of the Psalmists themselves but also about the identification of their persecuting enemies. No satisfactory answer has been given by those who following Smend’s hypothesis, which explains a collective „I” in the Psalms, considered the persecuted to be the devout (hasîdîm) Israelites and the persecuting enemies to be the disloyal Israelites who abandoned their Law (Rahlfs). No sufficient answer has been also given in the studies of those who, regarding a cult the origin of the Psalms, considered „enemies” to be: either sorcerers bringing about misfortunes on the others (Mowinckel), or foreign enemies of Israel whom the Israelit kings intended to defeat with Jahve’s help (Birkenland), or the false accusers of the innocent (Schmidt), or the ones who chased those who sought sanctuary in the temple (Delekat) or demanded a righteous judgement (Beyerlin). After a critical examination of the above-mentioned opinions the author presented different definitions of „enemies” as well as various changes occuring in the Psalms as regards a denotation of „enemies” and their hostile activities. On the grounds of this material and especially on the grounds of contents of the prayers of the persecuted the author arrieved at the conclusion that „enemies” in the Psalms were anonymous private individuals who intended consciously or unconsciously to dissuade the Psalmist (Balla) from a fidelity to Jahve and His Testament.